We know the derivative of e^{x}, which is e^{x}.
(e^{x})' = e^{x}
We can find the derivative of e^{2x} using chain rule.
If y = e^{2x}, find ᵈʸ⁄dₓ.
y = e^{2x}
Let t = 2x.
Then, we have
y = e^{t}
Now, y = e^{t }and t = 2x. That is, y is a function of t and t is a function of x.
By chain rule, the derivative of y with respect to x,
Substitute y = e^{t} and t = 2x.
Substitute t = 2x.
Therefore,
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Apr 16, 24 09:28 AM
Apr 15, 24 11:17 PM
Apr 14, 24 07:56 AM